Estudio comparado de las construcciones subordinadas generativas que expresan relaciones concesivas en ruso y en español - Guzmán Tirado, Rafael; Quero Gervilla, Enrique F. (Eslavística Complutense, 2007)
The aim of this article is to study how subordinated sentences are organized in Russian and Spanish. The theory used in this analyze is based on that of A.M. Lomov in Russia and Rafael Guzmán Tirado and E. F. Quero Gervilla in Spain. The proposed theory is founded on the principle that all subordinated sentences can be analyzed as part of a whole complex given that “In all subordinated sentences there is a situation that generates and a situation that is generated”. In this article we use this principle to analyze subordinated concessive sentences in Russian and Spanish